Internet connectivity disruption in Kuwait (Kuwait) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Kuwait. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KW-2026-0041. Severity: critical. Confidence: 67%